Analysis of Active Fire Protection System in Building X of Yogyakarta City - Julita Nuratira; Julian Dwi Saptadi (Universitas Ahmad Dahlan, 2025)
Background: A fire is a disaster that can occur at any time and bring material loss, environmental damage, and loss of life. In 2024, in the city of Yogyakarta, there will be 30 cases of fires in buildings that function as residences. One of the buildings at risk of fire is the hotel building. Suara Muhammadiyah (SM) Tower as a hotel has a potential fire hazard including coming from the kitchen, electrical panel room and electrical short circuit. This study aims to analyze the active fire protection system at “X” Yogyakarta. Methods: This type of research is a qualitative research that uses a case study approach. In this study, the total number of informants involved was 3 people, consisting of 1 manager as a key informant, 1 head of engineering as the main informant and 1 security person as a supporting informant. Results: The results of the study show that the “X” Yogyakarta building has a complete active protection system such as alarms and detectors, sprinklers, hydrants and fire extinguishers. However, there are active protection systems that do not meet the applicable reference standards. Conclusion: The active fire protection system in the “X” Yogyakarta Building is mostly in accordance with the Regulation of the Minister of Public Works (Permen PU) No. 26 of 2008. However, there are still four partially functional elements and one non-functional element